OECD Extended Regional Typology The Economic Performance of Remote Rural Regions - Brezzi, Monica (OECD Regional Development Working Papers, 2011)
To account for differences among rural and urban regions, the OECD s established a regional typology, classifying TL3 regions as predominantly urban (PU), intermediate (IN) or predominantly rural (PR) (OECD, 2009). This typology, based essentially on the percentage of regional population living in urban or rural communities, has proved to be meaningful to better explain regional differences in economic and labour market performance. However this typology does not take into account the presence of economic agglomerations if they happen to be in neighbouring regions. For example, a region is classified as rural or intermediate regardless its distance from a large urban centre where labour market, access to services, education opportunities and logistics for firms can be wider. Previous work reveals great heterogeneity in economic growth among rural regions and the distance from a populated centre could be a significant factor explaining these differences.